The Effectiveness of the Implementation of the Non-Cash Food Assistance Program in Poverty Alleviation Efforts - Amalia, Hikmatul; Nur Badriah, Irna; Permana, Ipik; Moh Sutarjo (ann4publisher@gmail.com, 2024)
This study aims to see how effective the implementation of the Non-Cash Food Assistance Program is in the Greged District, Cirebon Regency, and identify challenges and obstacles in its implementation. This study uses a qualitative research method with a descriptive analysis approach. The descriptive approach of analysis is used to obtain and select data that is relevant, up-to-date, unique, and related to the formulation of the problem or research question. This analysis uses all the data collected through various methods, such as observation and in-depth interviews. The researcher concluded that the implementation of the BPNT program in Greged District, Cirebon Regency, has not been effective because it shows several weaknesses and advantages. Key weaknesses include untimely disbursement of aid that is often late and a lack of effective oversight procedures for cash aid. On the other hand, no fee is charged to the beneficiary family (KPM). Although this program is easy for KPM to understand, there are problems with the accuracy of the target of aid recipients due to inaccurate data. Although it is not yet fully effective and still needs improvement, the BPNT program in the Greged District has helped the community meet food needs and contribute to poverty alleviation